2003
DOI: 10.1016/s0022-5347(05)63978-x
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Staghorn Calculi: The Role of Extracorporeal Shock Wave Lithotripsy Monotherapy With Special Reference to Ureteral Stenting

Abstract: ESWL monotherapy was an efficient and safe modality for the treatment of staghorn calculi in children. Stented patients had fewer major complications and a shorter hospital stay. Prophylactic ureteral stenting is advisable before ESWL for staghorn calculi in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Al-Busaidy et al [13] treated 42 children with staghorn stones using SWL. They observed no complications in those patients who were stented.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Busaidy et al [13] treated 42 children with staghorn stones using SWL. They observed no complications in those patients who were stented.…”
Section: Discussionmentioning
confidence: 99%
“…Higher success rates have been achieved in the treatment of smaller stones.A renal pelvis stone smaller than 2 cm in diameter will be an ideal choice for ESWL treatment. [18][19][20][21][22][23] Dimensions, location, and composition of the stone, anatomy of the renal calyx, superposition of bone on ureter are the most important factors effecting success rates of ESWL.…”
Section: Discussionmentioning
confidence: 99%
“…Stone-free rates of 67-93 % in short-term and 57-92 % in long-term followup studies have been reported [4,17,18]. Consequently, ESWL can be indicated in children with a larger stone volume, and the placement of a ureteral stent before or after ESWL is generally unnecessary [18,[20][21][22][23][24][25]. The mean number of shock waves for each treatment is about 1,800 and 2,000 (up to 4,000 if needed) and the mean power set varies between 14 and 21 kV.…”
Section: Conservative Management Of Acute Stone Episodementioning
confidence: 99%
“…A general recurrence rate of 2-44 % has been reported for children after ESWL; the residual stone growth is between 23 and 33 % [17,22,24,25]. In contrast, the recurrence rate in adults is only between 8 and 10 %, and the residual stone growth averages 22 %.…”
Section: Conservative Management Of Acute Stone Episodementioning
confidence: 99%
See 1 more Smart Citation